Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2053-1591/ab7f11
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency metamaterial with strong toroidal dipole response

Abstract: This paper designs a planar electromagnetically induced transparency (EIT) metamaterial, which comprises an asymmetric ellipse split resonance ring (AESRR) and cut wire (CW). The proposed EIT metamaterial works in the wide range of incident angles and has polarization-sensitive at two transmission dips. The frequency of transparency peak is 10.67 GHz and maintains a high qualityfactor (180.84). By calculating the multipole's radiated power, it can be found that the toroidal dipole response is enhanced, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Figure 12 A shows the variation of the effective RI with wavelength, whereas Figure 12 B illustrates the variation of the group index with change in parameter g. The inset picture indicates the MM geometry. Slow light phenomenon in toroidal EIT based MM has also been reported in another recent study ( Shen et al., 2020 ). They reported the variation of group index and the imaginary part of RI with frequency.…”
Section: Applications Of Toroidal Eitsupporting
confidence: 77%
See 2 more Smart Citations
“…Figure 12 A shows the variation of the effective RI with wavelength, whereas Figure 12 B illustrates the variation of the group index with change in parameter g. The inset picture indicates the MM geometry. Slow light phenomenon in toroidal EIT based MM has also been reported in another recent study ( Shen et al., 2020 ). They reported the variation of group index and the imaginary part of RI with frequency.…”
Section: Applications Of Toroidal Eitsupporting
confidence: 77%
“…Adapted with permission from ( Han et al., 2018 )© The Optical Society, Figures 7 G–7I). Reprinted from ( Li et al., 2015 ), with the permission of AIP Publishing., Figures 7 J–7L) Adapted from ( Shen et al., 2020 ) with full permission. …”
Section: Excitation Of Toroidal Dipole Based Eitmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al observed EIT via combination of an asymmetric elliptical SRR and cut wires 36 . The combination resulted in an EIT window in the GHz range and the combined structure demonstrated toroidal behaviour 38 . Dynamic manipulation of EIT effect has also been reported in a graphene loaded all dielectric meta surfaces 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, in order to create a single-band EIT-MM, the requirement is an MM structure consisting of, at least, two different types of resonators [26,27]. So far, to our knowledge, most of the multi-band EIT-MMs have exploited more than three different types of resonators in the structure [28][29][30].…”
Section: Introductionmentioning
confidence: 99%